Climate (in)action? The relationship between CEO early-life experiences and corporate climate policies - Wiebke Szymczak; Simone A. Wagner; Timo Busch (Ecological Economics, 2025)

Biodiversity finance: Measuring and managing biodiversity in companies and financial markets - Enrico Benetto; Timo Busch; Francesca Verones; Richard Wood (Journal of Industrial Ecology, 2025)

Assessing company sustainability impact: Status quo and way ahead - Timo Busch; Brigitte Bernard‐Rau; Hendrik Brosche (Journal of Industrial Ecology, 2025)
The transition to a sustainable economy requires investments in companies capable of driving real‐world transformations. Impact assessments are central to this, yet existing company impact assessment tools for impact investing lack the necessary methods and data to determine the significance of environmental and social impacts. This paper addresses this gap by first exploring the life cycle assessment (LCA) literature on LCA logics and their application in company impact assessment tools. Second, we examine the conceptual and practical availability of absolute sustainability indicators for investment purposes. Our findings show that while LCA logics provide a valuable foundation for assessing the significance of company impacts, important gaps remain in allocating macro‐level thresholds to the company level. Moreover, while environmental absolute sustainability indicators are conceptually advanced, their practical application is hindered by data limitations, restricting their usability for investors. Social absolute sustainability indicators lack clear impact pathways for translating macro‐level issues into actionable company‐level indicators, which is further constrained by data gaps. In light of these findings, we emphasize the distinct requirements of the environmental and social dimensions in advancing the assessment of the significance of company impacts. To effectively address these needs and enhance impact investment practices, we highlight the importance of interdisciplinary research, the regulatory and practical adoption of absolute sustainability approaches, and improved data integration.

Raising the bar: What determines the ambition level of corporate climate targets? - Clara Privato; Matthew P. Johnson; Timo Busch (Climatic Change, 2024)
Since the launch of the Science Based Targets initiative (SBTi), we have witnessed a steady increase in the number of companies committing to climate targets for large-scale reduction of greenhouse gas (GHG) emissions. While recent studies present various methodologies for establishing climate targets (e.g., sectoral decarbonization approach, near-term, long-term, net zero), we still don’t understand the explanatory factors determining the level of ambition companies demonstrate in target setting. In this paper, a two-stage qualitative study is conducted with a sample of 22 companies from five countries. First, these companies’ publicly disclosed climate targets are evaluated according to four target ambition criteria: target type, scope, timeframe, and temperature alignment. Secondly, multiple explanatory factors for target setting were identified during the content analysis of the interviews to see how present these factors appear in the ambition levels. Within companies with highly ambitious climate targets, the findings indicate that certain factors are highly present, including leadership engagement, continual management support, employee involvement, participation in climate initiatives, and stakeholder collaboration. Conversely, none of these key factors are highly present in companies with less ambitious climate targets. Rather, these companies strongly identify the initiating factors of market-related pressures and non-market stakeholder influence as being the driving forces behind their target setting. This paper contributes to the literature on corporate responses to climate change by expanding our understanding of explanatory factors for different corporate climate target ambition levels.

Corporate carbon performance data: Quo vadis? - Timo Busch; Matthew Johnson; Thomas Pioch (Journal of Industrial Ecology, 2022)
Corporate carbon performance (CCP) has become a central topic in political, financial, and academic domains. At the same time, several characteristics of CCP data, including comparability and consistency, remain unresolved. The literature has extensively covered issues regarding the comparability of CCP data from a firm‐internal perspective. However, it has not yet examined the consistency of CCP data between third‐party data providers. This article investigates the degree of CCP data consistency between third‐party providers according to three dimensions: scope (i.e., direct and indirect emissions), scheme (i.e., mandatory and voluntary reporting schemes), and source (i.e., data stemming from corporate reports and from third‐party estimation methods). The results reveal that data on direct emissions are more consistent than data on indirect emissions, and they are especially inconsistent for Scope 3. Second, mandatory and voluntary reporting schemes do not substantially improve the consistency of CCP data, which is surprising. Third, third‐party estimations are less consistent as compared to data stemming directly from corporate reports; however, the combination of Scopes 1 and 2 third‐party estimated data raises consistency levels. On the basis of these results, we conclude the following key implications: academic researchers must be mindful of the consistency of CCP data, because it can significantly affect empirical results, corporate management should avoid situations where different CCP data are communicated externally, investors should engage firms to follow a standardized approach, data providers should increase the transparency about their estimation methods, and policy makers need to be aware of the importance of a sound and standardized methodology to determine CCP.

Predicting Fluid Flow Regime, Permeability, and Diffusivity in Mudrocks from Multiscale Pore Characterisation - Amirsaman Rezaeyan; Vitaliy Pipich; Jingsheng Ma; Leon Leu; Timo Seemann; Gernot Rother; Lester C. Barnsley; Andreas Busch (Transport in Porous Media, 2022)
In geoenergy applications, mudrocks prevent fluids to leak from temporary (H 2 , CH 4 ) or permanent (CO 2 , radioactive waste) storage/disposal sites and serve as a source and reservoir for unconventional oil and gas. Understanding transport properties integrated with dominant fluid flow mechanisms in mudrocks is essential to better predict the performance of mudrocks within these applications. In this study, small-angle neutron scattering (SANS) experiments were conducted on 71 samples from 13 different sets of mudrocks across the globe to capture the pore structure of nearly the full pore size spectrum (2 nm–5 μm). We develop fractal models to predict transport properties (permeability and diffusivity) based on the SANS-derived pore size distributions. The results indicate that transport phenomena in mudrocks are intrinsically pore size-dependent. Depending on hydrostatic pore pressures, transition flow develops in micropores, slip flow in meso- and macropores, and continuum flow in larger macropores. Fluid flow regimes progress towards larger pore sizes during reservoir depletion or smaller pore sizes during fluid storage, so when pressure is decreased or increased, respectively. Capturing the heterogeneity of mudrocks by considering fractal dimension and tortuosity fractal dimension for defined pore size ranges, fractal models integrate apparent permeability with slip flow, Darcy permeability with continuum flow, and gas diffusivity with diffusion flow in the matrix. This new model of pore size-dependent transport and integrated transport properties using fractal models yields a systematic approach that can also inform multiscale multi-physics models to better understand fluid flow and transport phenomena in mudrocks on the reservoir and basin scale.

Climate change—that is not real! A comparative analysis of climate-sceptic think tanks in the USA and Germany - Timo Busch; Lena Judick (Climatic Change, 2021)
The science is clear: climate change is real. In 2015, 195 countries adopted the global climate deal in Paris. Nonetheless, numerous well-organized conservative think tanks (CTTs) deny that climate change is happening. We ask what kind of counterclaims are used by climate-sceptic CTTs and to what extent these counterclaims change over time. We analyse about 2500 blog articles from prominent CTTs in the USA and Germany between 2008 and 2016. Our results show that sceptical arguments about climate policy and science dominate the countermovement. At the same time, we detect that the prevalence of counterclaims is CTT-specific and that US think tanks show a greater variability compared to their German counterparts. In a surprising outcome, we find that the Paris Agreement did not affect the climate denial movement. Based on these insights, we discuss our contributions to social movement research in the climate change denial context and derive conclusions for pro-climate campaigns.

Industrial ecology, climate adaptation, and financial risk - Timo Busch (Journal of Industrial Ecology, 2020)
Climate adaptation has become an important topic for risk management in companies. This article investigates the usefulness of Industrial Ecology tools and concepts in this context. The conclusion is that the established tools and concepts were not designed with the purpose of assisting managers in the climate adaptation and related financial risk context. Nevertheless, the tools and concepts offer plenty of aspects and features that are helpful for the assessment and management of climate risks. The tools primarily provide guidance for the managerial decision‐making process, notably in terms of data handling. The concepts can be used as a starting point for developing new climate risk management frameworks.

Corporate Carbon and Financial Performance: A Meta‐analysis - Timo Busch; Stefan Lewandowski (Journal of Industrial Ecology, 2018)
Summary We use meta‐analytical techniques to address the question“ When does it pay to be green?” Existing meta‐studies in this research field cover a range of ecological issues and synthesize a variety of environmental performance measurements. This precludes a detailed examination of how differences in measurement approaches account for variations in empirical results. In order to conduct such an examination, we focus on only one ecological issue, climate change, and one particular operational performance dimension: corporate carbon performance as expressed by a firm's level of carbon dioxide (CO 2 ) emission equivalents. Our sample comprises 68 estimations from 32 empirical studies, covering a total of 101,775 observations. In addition to our examination of the causal relationship, we analyze whether differences in operationalizations of carbon performance and financial performance predetermine empirical outcomes. The meta‐analytic findings indicate that carbon emissions vary inversely with financial performance, indicating that good carbon performance is generally positively related to superior financial performance. The results show that relative emissions are more likely to produce statistically significant results than absolute emissions. Furthermore, market‐based measures of financial performance are more positively related to carbon performance than accounting‐based measures. We conclude that measurement characteristics, which were not analyzed in detail by previous meta‐studies, may present a great source of cross‐study variability.

Estimating Corporate Carbon Footprints with Externally Available Data - Bernhard Goldhammer; Christian Busse; Timo Busch (Journal of Industrial Ecology, 2017)
Summary Corporate carbon footprints (CCFs) are a core tool in greenhouse gas emissions reporting. Established approaches for CCF calculation are based on an internal perspective that requires detailed corporate information. However, many firms do not publish information about their emissions. We seek to close this data gap by estimating scope 1 and 2 CCFs from an external perspective. The study uses a regression analysis approach, using actual firm‐internally computed CCFs to assess their degree of predictability from the outside. Data were collected from 93 European companies belonging to the chemicals, construction and engineering, and industrial machinery sectors. As predictors, we use five measures that are computed with publicly available corporate data: firm size; level of vertical integration; capital intensity; centrality of production; and carbon intensity of the national energy mix. The analysis shows that significant explanatory power for the CCF can be observed for size, capital intensity, and centrality of production. The best estimation results are achieved when data from different sectors are integrated into a comprehensive all‐sector model, while accounting for sector‐specific emission intensities by means of dummy variables. With an adjusted R² value of 0.817, the proposed procedure estimates CCFs in an accurate, yet also efficient, manner. Moreover, the study enhances trust in the current CCF calculation practices by showing that their results are plausible from a third‐party perspective.

Dynamic imaging of mitochondrial membrane proteins in specific sub-organelle membrane locations - Timo Appelhans; Karin B. Busch (Biophysical Reviews, 2017)

The Island Logic: Scaling Up the Concept of Self‐preserving Autarky - Timo Busch; Alice Sakhel (Journal of Industrial Ecology, 2016)

Corporate Carbon Performance Indicators Revisited - Timo Busch (Journal of Industrial Ecology, 2010)

Corporate Carbon Performance Indicators - Volker H. Hoffmann; Timo Busch (Journal of Industrial Ecology, 2008)
Summary The dependency on carbon‐based materials and energy sources and the emission of greenhouse gases have been recognized as major problems of the 21st century. Companies are central to the effort to grapple with these issues due to the large material flows they process and their capabilities for technological innovation. It is important, on the one hand, to determine the individual stake companies have in these issues and, on the other, to measure companies' performance. Since the results of studies thus far have been ambiguous, we define four comprehensive and systematic corporate carbon performance indicators: (1) Carbon intensity is physically oriented and represents a company's carbon use in relation to a business metric. (2) Carbon dependency illustrates the change in physical carbon performance within a given time period. (3) Carbon exposure reveals the financial implications of using and emitting carbon. (4) Carbon risk estimates the change in financial implications of carbon usage within a given time period. On the basis of these general definitions, we specify the indicators for a standardized application that can support two important stakeholders in their decision making: policy makers, who can include such information when evaluating current climate policies and formulating future ones, and investors and financial institutions, which can compare companies with respect to their carbon performance and corresponding financial effects.

Carbon Constraints in the Fourteenth and Twenty‐first Centuries - Volker Hoffmann; Timo Busch (Journal of Industrial Ecology, 2007)